LINGUODIDACTIC PECULIARITIES OF STUDYING RUSSIAN REALITIES IN UZBEK LANGUAGE CLASSROOMS - Dildarkhon Urinbaevna Khashimova; Tatyana Borisovna Mikheeva (American Journals, 2023)
This article deals with the disclosure of the meaning of ethnocultural realities by translation and non-translation methods. To the translation method of semantization the author refers translation-interpretation, in which in addition to the equivalent in the native language students are informed about the coincidence or divergence in the scope of the meaning of lacunas. Also, we are talking about the translation-free method of semantization, which includes: demonstration of objects, gestures, actions, pictures, drawings, transparencies, slides and disclosure of the meanings of realia in Russian, for which can be used definitions - descriptions of the meaning of a new word by already known words.
Keywords: Realia, lacuna, semantization, visualization, interpretation, commentary, ethno-cultural studies, national culture, comparison of similar phenomena, facts of Russian history and culture, passive minimum, image-mediator.